Succinic semialdehyde dehydrogenase deficiency presenting with central hypothyroidism - Malak Ali Alghamdi (Clinical Case Reports, 2021)
Abstract Central hypothyroidism might be another clinical sign of SSADH deficiency which prompts urinary organic acid screening for GHB in central hypothyroidism patients. Studies on GABA and thyroid hormone interaction might be a concept of a new therapy.